1996
DOI: 10.1164/ajrccm/154.4_pt_2.s133
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Recognition by Mycoplasma pneumoniae and Pathologic Consequences

Abstract: Mycoplasma pneumoniae infection in the human is often followed by a transient autoimmune hemolytic disorder characterized by high titer autoantibodies to a carbohydrate antigen, the I antigen. Because the major host cell receptor for the Mycoplasma is the sialylated form of this antigen, it is likely that the immunologic disorder is initiated by the microbe-saccharide interaction. Here we review briefly knowledge on the autoantibodies and the structures and distribution of the saccharide antigens and receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Autoimmune hemolytic anemia (cold agglutinin disease) is the most famous indirect-type extrapulmonary manifestation due to M. pneumoniae infection for which the pathomechanism has been established, involving a cross-reaction between glycolipid antigens of M. pneumoniae and the I antigen on the erythrocyte surface [22,[42][43][44].…”
Section: Hematological (Hematopoietic System) Manifestationsmentioning
confidence: 99%
“…Autoimmune hemolytic anemia (cold agglutinin disease) is the most famous indirect-type extrapulmonary manifestation due to M. pneumoniae infection for which the pathomechanism has been established, involving a cross-reaction between glycolipid antigens of M. pneumoniae and the I antigen on the erythrocyte surface [22,[42][43][44].…”
Section: Hematological (Hematopoietic System) Manifestationsmentioning
confidence: 99%
“…Cold agglutinins were presumed to cause antibody mediated hemolysis in 10% of the patients [4]. Nevertheless, severe hemolysis is exceptional [5,6]. We report a case of severe autoimmune hemolytic anemia secondary to Mycoplasma pneumoniae infection in a 29-year-old man.…”
mentioning
confidence: 99%
“…The mechanism by which these auto-antibodies arise in M. pneumoniae infection is unknown. It has been suggested that the infective agent or its adhesins serve as immunological adjuvants for the host cell carbohydrate antigens (Feizi & Loveless, 1996). We raise the possibility that the anti-SGGL antibodies in the sera of patients might have been antiidiotypic antibodies.…”
Section: Cfdimentioning
confidence: 80%